2007
DOI: 10.1093/jac/dkm005
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of primary clarithromycin resistance in Helicobacter pylori strains over a 15 year period in Italy

Abstract: A 2-fold increase in primary clarithromycin resistance in H. pylori strains occurred during the last 15 years in Italy. A2143G remains the most prevalent point mutation involved, thus suggesting that new therapeutic strategies are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
67
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 95 publications
(76 citation statements)
references
References 10 publications
8
67
0
Order By: Relevance
“…Ultimately, HSpA displayed a less effective performance, since it was positive in 41 infected subjects (82 %) and the concordance with RT-PCR was poor (Cohen's k50.21; CI 0-0.498). Finally, RT-PCR found the A2143G mutation in 11 cases, with a prediction of treatment failure of 22 %, a value that is comparable to clarithromycin resistance reports in some areas of Italy (De Francesco et al, 2011), thus confirming the increasing trend of antibiotic resistances towards clarithromycin in Italy (Ierardi et al, 2013). In the control group, RT-PCR did not detect H. pylori genetic sequences in any sample.…”
supporting
confidence: 73%
“…Ultimately, HSpA displayed a less effective performance, since it was positive in 41 infected subjects (82 %) and the concordance with RT-PCR was poor (Cohen's k50.21; CI 0-0.498). Finally, RT-PCR found the A2143G mutation in 11 cases, with a prediction of treatment failure of 22 %, a value that is comparable to clarithromycin resistance reports in some areas of Italy (De Francesco et al, 2011), thus confirming the increasing trend of antibiotic resistances towards clarithromycin in Italy (Ierardi et al, 2013). In the control group, RT-PCR did not detect H. pylori genetic sequences in any sample.…”
supporting
confidence: 73%
“…However, in the same period a study by our group found a median value of 28.7% in two areas in Southern and Central Italy [9] . In 2007, in a retrospective study performed over a 15-year period in the same geographical area, we found a 10.2% prevalence of primary clarithromycin resistance in 147 patients in the 1990 period, whereas by 2004-2005 the resistance found in 178 patients had increased significantly, to 21.3% or 2-fold higher [10] . The phenomenon was found to be more evident in females.…”
Section: Prevalence Of Resistance To Clarithromycinmentioning
confidence: 85%
“…The use of increased PPI doses is another suggestion to improve the cure rate of triple therapies [4]. In Southern and Central Italy, where this study was performed, the prevalence rate of primary clarithromycin resistance has been found to be higher than 20% [17,18]. Based on these observations, we peformed this study to test the efficacy of 14-day triple therapy with either standard or double PPI doses for first-line H. pylori eradication.…”
Section: Discussionmentioning
confidence: 99%